Indiscriminated use of pesticides in the rocoto value chain (Capsicum pubescens) in Oxapampa - Gómez Galarza, Vilma E. (2021)
The research presents evidence of the intensive use of chemical pesticides along the links of the value chain of rocoto from the province of Oxapampa (Pasco Region) to the mercado de Lima. The value chain approach was used to analyze the production and supply of rocoto to Metropolitan Lima. The information gathering techniques were formal interviews, observation and review of current regulations on the use of pesticides. Oxapampa is the main supplier of fresh hot pepper to Metropolitan Lima. The results showed that all producers used chemical pesticides at harvest and postharvest, representing 22% of production costs. In the commercialization, the gatherers applied fungicides before sending the fresh rocoto to the Lima market. At the level of wholesalers and retailers, participation was evidenced by influencing decisions on the use of pesticides through the demands of rocoto fruits, of large size, color and without spots. The use of pesticides recommended for other crops was generalized, with prohibited active ingredients and restricted use in other countries (benomyl, paraquat and glyphosate). The practices in the management of pesticides in the links of production and marketing in the value chain of rocoto put at risk both the health of producers and consumers, the environment, and the continuity of this productive activity.